2009
DOI: 10.1111/j.1752-4571.2008.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed infections and the competitive fitness of faster‐acting genetically modified viruses

Abstract: Faster-acting recombinant baculoviruses have shown potential for improved suppression of insect pests, but their ecological impact on target and nontarget hosts and naturally occurring pathogens needs to be assessed. Previous studies have focused on the fitness of recombinants at the between-hosts level. However, the population structure of the transmission stages will also be decided by within-host selection. Here we have experimentally quantified the within-host competitive fitness of a fast-acting recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Our results of reduced fitness of SeXD1 as compared to SeUS1 are in agreement with those of Zwart et al (2009b), who found that an egt deletion mutant of AcMNPV was less fit in competition experiments with wild-type AcMNPV in Trichoplusia ni. These findings collectively suggest that egt has a role in virus multiplication, spread or packaging in the insect.…”
Section: Discussionsupporting
confidence: 94%
“…Our results of reduced fitness of SeXD1 as compared to SeUS1 are in agreement with those of Zwart et al (2009b), who found that an egt deletion mutant of AcMNPV was less fit in competition experiments with wild-type AcMNPV in Trichoplusia ni. These findings collectively suggest that egt has a role in virus multiplication, spread or packaging in the insect.…”
Section: Discussionsupporting
confidence: 94%
“…Baculovirus biology suggests that the number of virus particles that initiates infections is probably small (Zwart et al 2009a(Zwart et al , 2009b, and so we used probabilistic models that inherently allow for demographic stochasticity. The models track the replication and destruction of virions, as well as the immune cells that are destroyed along with the virions.…”
Section: Model Constructionmentioning
confidence: 99%
“…parasite‐induced host mortality) correlates with the extent of parasite resource exploitation. Adaptive benefits of resource exploitation include the positive correlation with transmission (Fraser et al ., ; de Roode et al ., ; Råberg, ), and a within‐host competitive advantage in coinfection (de Roode et al ., ; Bell et al ., ; Ben‐Ami et al ., ; Zwart et al ., ). Here, we focus on the latter adaptive benefit to study the evolution of virulence and immunosuppression.…”
Section: The Modelmentioning
confidence: 99%